Geochemistry of ice in frost mounds in the valley of the River Sentsa (Oka plateau, East Sayan) - S. V. Alekseev; L. P. Alekseeva (Лëд и снег, 2018)
Te authors examined the chemical composition of underground ice sampled from the frost mounds located in the loose (unconsolidated) sediments of the Sentsa River valley (Oka plateau, Eastern Sayan) with the purpose of reconstruction the formation history of these cryogenic creations. Numerous frost mounds of various sizes are mainly composed of alternating icy loams, sandy loams, and lenses of pure ice. Samples of underground ice taken in the outcrops of the river ledges and cores from wells together with samples of river and lake waters were analyzed by traditional hydrochemical techniques (methods) in the center "Geodynamics and geochronology" (Institute of the Earth's Crust of the Siberian branch of RAS, Irkutsk). It was found that the chemical composition of pure ice melts from lenses and layers of the frost mounds is hydrocarbonate calcium (HCO3 Ca, SO4-HCO3 Ca and NH4-HCO3 Ca) with mineralization of 6.5 – 15.6 mg/L, pH = 5.6÷6.1. Mineralization of melts of texture-forming ice, taken from icy ground (i.e. with fractions of enclosing loams) was much higher – from 50 to 792.5 mg/L. River and lake water is ultra-fresh with 99–132 mg/L salinity, and according to geochemical type it is hydrocarbonate calcium (HCO3 Ca). Te specifc features of chemical composition of the underground ice (high content of ammonium salts and sulfates) depend on a water-rock interaction, the presence of organic matter in the loose (unconsolidated) sediments and a repeated volcanic activity in the late Pleistocene–Holocene. Te frost mounds are confned to a lacustrine sediments area in the backwater zone that was formed by the Late Pleistocene terminal moraine. Teir formation in the Holocene took place as a result of segregational ice formation during freezing of water-saturated lake sediments, and, presumably, repeated injections of underground waters of the under-channel and ﬂoodplain aquifers hydraulically connected with river waters. Tus, the genesis of the studied frost mounds is probably a mixed segregation-injection process.